Elucidating Mitochondrial DNA Markers of Ogura-Based CMS Lines in Indian Cauliflowers (Brassica oleracea var. botrytis L.) and Their Floral Abnormalities Due to Diversity in Cytonuclear Interactions - Singh, Saurabh; Bhatia, Reeta; Kumar, Raj; Behera, Tusar K.; Kumari, Khushboo; Pramanik, Achintya; Ghemeray, Hemant; Sharma, Kanika; Bhattacharya, R. C.; Dey, Shyam S. (Frontiers in Plant Science, 2021)
Mitochondrial markers can be used to differentiate diverse mitotypes as well as cytoplasms in angiosperms. In cauliflower, cultivation of hybrids is pivotal in remunerative agriculture and cytoplasmic male sterile lines constitute an important component of the hybrid breeding. In diversifying the source of male sterility, it is essential to appropriately differentiate among the available male sterile cytoplasms in cauliflower. PCR polymorphism at the key mitochondrial genes associated with male sterility will be instrumental in analyzing, molecular characterization and development of mitotype-specific markers for differentiation of different cytoplasmic sources. Presence of auto and alloplasmic cytonuclear combinations result in complex floral abnormalities. In this context, the present investigation highlighted the utility of organelle genome based markers in distinguishing cytoplasm types in Indian cauliflowers and unveils the epistatic effects of the cytonuclear interactions influencing floral phenotypes. In PCR based analysis using a set of primers targeted to orf-138, 76 Indian cauliflower lines depicted the presence of Ogura cytoplasm albeit the amplicons generated exhibited polymorphism within the ofr-138 sequence. The polymorphic fragments were found to be spanning over 200-280 bp and 410-470 bp genomic regions of BnTR4 and orf125, respectively. Sequence analysis revealed that such cytoplasmic genetic variations could be attributed to single nucleotide polymorphisms and insertion or deletions of 31/51 nucleotides. The cytoplasmic effects on varying nuclear-genetic backgrounds rendered an array of floral abnormalities like reduction in flower size, fused flowers, splitted style with the exposed ovule, absence of non-functional stamens, and petaloid stamens. These floral malformations caused dysplasia of flower structure affecting female fertility with inefficient nectar production. The finding provides an important reference to ameliorate understanding of mechanism of cytonuclear interactions in floral organ development in Brassicas. The study paves the way for unraveling developmental biology of CMS phenotypes in eukaryotic organisms and inter-genomic conflict in plant speciation.